The bandgap of sulfur-doped Ag2O nanoparticles. Issue 3 (4th January 2023) - De, Arup Kumar; Kamal, Neha; Kumar, Uttam; Jatav, Neha; Sinha, Indrajit
Abstract : A narrow band gap restricts photocatalytic applications of Ag2 O nanoparticles, but appropriate doping can favorably modify this aspect. Abstract : A narrow band gap restricts photocatalytic applications of Ag2 O nanoparticles, but appropriate doping can favorably modify this aspect. Given this, density functional theory (DFT) calculations were conducted, revealing that substitutional sulfur doping of Ag2 O could increase its bandgap and stabilize oxygen vacancies. A hydrothermal precipitation protocol was employed to prepare sulfur-doped (S-doped) Ag2 O nanoparticles. The band gap of the prepared nanoparticles increased to 1.89 eV with 1.25-mole percent S-doping. XPS analysis of the samples also revealed that S-doping increased oxygen vacancies in the prepared Ag2 O nanoparticles. Furthermore, S-doping caused a major shift in the valence band position to a negative value. These doped Ag2 O nanoparticles showed an enhanced visible-light photocatalytic activity towards rhodamine B (RhB) degradation.